Institutions and Development : The Interaction between Trade Regime and Political System - Josef Falkinger; Volker Grossmann (Institute for the Study of Labor (IZA), 2004)
This paper argues that openness to goods trade in combination with an unequal distribution of political power has been a major determinant of the comparatively slow development of resource- or land-abundant regions like South America and the Caribbean in the nineteenth century. We develop a two-sector general equilibrium model with a tax-financed public sector, and show that in a feudal society (dominated by landed elites) productivity-enhancing public investments like the provision of schooling are typically lower in an open than in a closed economy. Moreover, we find that, under openness to trade, development is faster in a democratic system. We also endogenize the trade regime and demonstrate that, in political equilibrium, a land-abundant and landowner dominated economy supports openness to trade. Finally, we discuss empirical evidence which strongly supports our basic hypotheses.
Keywords: H50; F43; N10; O10; N16; 330; economic development; institutions; political system; public education; trade; Entwicklung; Politik der offenen Tür; Aussenwirtschaftspolitik; Politisches System; Theorie; Welt